2020
DOI: 10.3390/en13194993
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady Flow Field Characterization of Effusion Cooling Systems with Swirling Main Flow: Comparison Between Cylindrical and Shaped Holes

Abstract: The presence of injectors with strongly swirled flows, used to promote flame stability in the combustion chambers of gas turbines, influences the behaviour of the effusion cooling jets and consequently of the liner’s cooling capabilities. For this reason, unsteady behaviour of the jets in the presence of swirling flow requires a characterization by means of experimental flow field analyses. The experimental setup of this work consists of a non-reactive single-sector linear combustor test rig, scaled up with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…More recently, Huang et al [11] performed a multi-objective optimization of the laidback fan-shaped hole as applied to the turbine guide suction surface by taking the film cooling effectiveness and the discharge coefficient into consideration. Lenzi et al [12] revealed the unsteady flowfield characterization of a shaped-hole effusion system in the swirling mainstream from detailed experimental tests. Kim et al [13] investigated the influence of fan-shaped hole position and jet-to-crossflow density ratio on the film cooling performance.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Huang et al [11] performed a multi-objective optimization of the laidback fan-shaped hole as applied to the turbine guide suction surface by taking the film cooling effectiveness and the discharge coefficient into consideration. Lenzi et al [12] revealed the unsteady flowfield characterization of a shaped-hole effusion system in the swirling mainstream from detailed experimental tests. Kim et al [13] investigated the influence of fan-shaped hole position and jet-to-crossflow density ratio on the film cooling performance.…”
Section: Introductionmentioning
confidence: 99%